Circular No. 7 of the year 2024 On The Nature Of The Tax Imposed On The Real Estate Investment Activity - Ministry of Finance (The Middle East Library for Economic Services, 2025)
As it has been observed that some taxpayers who carry out the real estate investment activity, whether natural or juridical persons, included a clause in the sale contracts of their units, stipulating that the buyer shall bear the real estate disposition tax imposed on the unit subject of contract, and that the relevant amounts shall be collected from buyers under the designation “real estate disposition tax”,